Mapping IoT Applications in the Textile Industry: A Bibliometric Study using Biblioshiny and VOSviewer - Kurnia, Deni; Sutanto, Agus; Fakhrurroja, Hanif; Son, Lovely (Universitas Muhammadiyah Yogyakarta, 2025)
The rapid advancement of technology, particularly the Internet of Things (IoT), has had a transformative impact on various industries, including the textile sector. IoT facilitates real-time data collection, monitoring, analysis, and decision-making, thereby enhancing efficiency, productivity, and resource sustainability. However, a comprehensive bibliometric study of IoT applications in the textile industry has yet to be undertaken. To address this research gap, this study employs bibliometric methods using the Biblioshiny R package and VOSviewer to examine research trends, key contributors, and emerging themes. By analyzing 177 relevant publications from 2015 to 2025, the study identifies major research directions, influential authors, leading institutions, and evolving areas of interest. The findings highlight a growing research focus on IoT-driven textile innovations, particularly the development of electronic textiles (e-textiles), which integrate electronic components into wearable devices for human use. This positioning of e-textiles at the forefront of smart wearable technology underscores their significance as a critical area of exploration within contemporary textile engineering. Furthermore, China, the United States, and India emerge as the predominant contributors to this research domain. The insights derived from this study offer valuable guidance for researchers, industry professionals, and policymakers, supporting future advancements and innovations in IoT applications within the textile industry.